Sea otter rescue - Eszterhas, Suzi (Eszterhas, Suzi. Wildlife rescue, 2016)
Offers an illustrated look at the Alaska SeaLife Center's Wildlife Rescue Team and their efforts to treat young, orphaned sea otters.